LDLR C1725T Gene Polymorphism Frequency in Type 2 Diabetes Mellitus Patients With Dyslipidemia - Eroglu, Zuhal (J Clin Med Res, 2016)
BACKGROUND: Dyslipidemia has a substantial role in the development of cardiovascular diseases in patients with type 2 diabetes mellitus (T2DM). Determining the genetic profile of T2DM patients with dyslipidemia is important in order to reduce the risk of microvascular and macrovascular complications. Low-density lipoprotein receptor (LDLR) plays a critical role in plasma lipoprotein hemostasis. LDLR mutations/polymorphisms cause changes at the lipoprotein level. The objective of this study is to determine the frequency of LDLR (rs179989) polymorphisms in Turkish T2DM patients with dyslipidemia. METHODS: The study group consisted of 217 T2DM patients with dyslipidemia including 28 cases with myocardial infarction and 212 healthy controls. Genomic DNA was isolated from venous blood samples and genotype analysis was carried out on the LightCycler(®) 480 instrument. The χ(2) test was used to compare genotype distributions. RESULTS: There were no significant differences in the frequency or allelic distribution of the LDLR C1725T (rs1799898) genotype between the type 2 diabetic dyslipidemia patients and the control group (P > 0.05). CONCLUSION: LDLR C1725T polymorphism was not associated with lipid parameters, and dyslipidemia in T2DM patients.